MEASURING THE PRESSURE IN DYNAMIC MODE - Vladimir Kononov (Сучасні інформаційні системи, 2019)
The subject study of the article is to measure the pressure in the dynamic mode used in parts of the regional center of standardization and metrology during the verification and calibration of measuring equipment and during their operation. The article is research process of measuring the pressure in the dynamic mode and the principles of perspective on device verification and calibration of pressure. The problem to be solved is justification of technical solutions and their implementation in practice. It will improve measurement accuracy pressure measurement used for verification and calibration of the device on checking and calibration of pressure by applying a generalized block diagram of pressure offered. The article shows the Dynamic mode of pressure; dependence of dynamic properties of measurement tools on the nature of changes in the value measured; research of dynamic characteristics of pressure; the input error measuring pressure in dynamic mode; block diagram and principle of the prospective device on checking and calibration of pressure which are being developed. Conclusion: The proposed technical solutions should be used as the modernization of existing pressure meters, and in the creation of promising samples of pressure meters.